An introductory systems thinking toolkit for civil servants - Government, UK (UK Government Office for Science, 2022)
This document is a an Introductory Toolkit for for civil servants. It is one component of a suite of documents that aims to act as a springb oard into systems thinking for civil servants unfamiliar with this app roach. These documents introduce a small sample of systems thinking co ncepts and tools, chosen due to their accessibility and alignment to c ivil service policy development, but which is by no means comprehensiv e. They are intended to act as a first step towards using systems thin king approaches to solve complex problems and the reader is encourage to explore the wider systems thinking field further.